Impact of COVID-19 on UK radiology training: a questionnaire study. Issue 11 (November 2020) - Veerasuri, S.; Vekeria, M.; Davies, S.E.; Graham, R.; Rodrigues, J.C.L.
Abstract : AIM: To understand the impact of COVID-19 on radiology trainee experience and well-being. MATERIALS AND METHODS: A questionnaire designed to capture the impact of COVID-19 on radiology training, working patterns, and well-being was sent to all speciality trainees in a regional UK radiology school. The survey was distributed at the beginning of May 2020 and responses collected over 2 weeks. Trainees were questioned about changes that had occurred over a time period starting at the beginning of the COVID-19 pandemic. All survey responses ( n =29) were anonymised and the results were subsequently analysed. RESULTS: Sixty-two percent (29 of 47) of trainees within the deanery, who were spread across seven different hospital sites, responded to the questionnaire. All trainees felt that overall radiology workload had decreased in response to COVID-19. Seventy-two percent (21/29) stated that their workload had significantly decreased. Seventy percent (19/27) reported decreased subspecialty experience, and 19% (5/27) reported a complete lack of subspecialty training. Twenty-four percent (7/29) of trainees were redeployed from radiology to clinical ward-based work. Forty-eight percent reported experiencing a worsening in their well-being compared to before the pandemic. CONCLUSION: The first wave of the COVID-19 pandemic had a significant impact on training and well-being. Lessons learnt from this report should help prepare for a second-wave of COVID-19 or future pandemics. Highlights: Radiology workload had significantly decreased during COVID-19 pandemic. Covid-19 had a significant impact on radiology trainee reporting and experience. Overall trainee well-being has significantly worsened during the pandemic. Our results could help prepare for second-wave of COVID-19 or future pandemics.